1989
DOI: 10.1093/tropej/35.2.55
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Diarrhoea: A Preliminary Report on Clinical Features and Dietary Therapy in Bangladeshi Children

Abstract: Twenty-six infants and children aged 2-24 months suffering from diarrhoea for more than 2 weeks were studied in the ICDDRB's Dhaka Treatment Centre. They presented with watery diarrhoea and the majority had moderate dehydration. A stool pathogen was isolated in only one infant. Systemic infections co-existed in half of the subjects. Subjects between 4 and 12 months of age were moderately malnourished. The remainder were severely malnourished. A range of therapeutic diets were given according to the clinical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…Alternatively, it might reflect increased fluid loss due to a less efficient absorptive mechanism. In our previous study, 88% of children with persistent diarrhoea lost body weight during their illness (21). The present study showed enhanced clinical recovery with zinc supplementation in the children who were underweight (Ͻ70 weight for age), the group at greatest risk for morbidity and mortality.…”
Section: Discussionsupporting
confidence: 65%
“…Alternatively, it might reflect increased fluid loss due to a less efficient absorptive mechanism. In our previous study, 88% of children with persistent diarrhoea lost body weight during their illness (21). The present study showed enhanced clinical recovery with zinc supplementation in the children who were underweight (Ͻ70 weight for age), the group at greatest risk for morbidity and mortality.…”
Section: Discussionsupporting
confidence: 65%
“…9,15 The case fatality in this study was 8.3% which is similar to studies from India and Bangladesh. 16,17 Though maximum number of PD was observed in infancy, highest mortality was in the age group of one to five yrs. This is consistent with the observation from Bangladesh 1 , though higher mortality in younger age group has been reported from India and Turkey.…”
Section: Discussionmentioning
confidence: 97%
“…If this is unsuccessful a comminuted chicken diet is given. 22 In our study, we used comminuted chicken diet because this diet is free of fibres and complex carbohydrates. This was intended to examine the effects of Benefiber supplementation.…”
Section: Discussionmentioning
confidence: 99%